EXTH-67. PRECLINICAL ASSESSMENT OF THE EFFICACY OF MPT0B640, AN ORALLY BIOAVAILABLE SMALL MOLECULE HSP90 INHIBITOR, AGAINST GLIOMAS. (14th November 2022) - Sharma, Pratibha; Xu, Jihong; Chen, Xiaohua; Huo, Longfei; Ju, Zhenlin; Li, Ziyi; Ban, Kechen; Seah, Ethan; Sampath, Deepa; Puduvalli, Vinay
Abstract: BACKGROUND: Heat-shock protein 90 (HSP90), an evolutionary conserved protein, is a key member of the epichaperome complex involved in maintenance of protein homeostasis during non-stress and stress conditions. It is overexpressed in gliomas and supports tumor cell survival and resistance. Hsp90 inhibition can impact several pathways essential for glioma cell survival and overcome tumor heterogeneity. Here, we examined the activity and toxicity profile of MPT0B640, an orally bioavailable Hsp90 inhibitor, against gliomas and its ability to cross the blood-brain barrier (BBB). METHODS: Using genetically heterogeneous glioma stem-like cell (GSC) lines, we determined the effects of MPT0B640 on cell proliferation (Cell Titre Glo assay), apoptosis induction and cell cycle changes (flowcytometry; AnnexinV/PI staining), and alterations in protein expressions (western blot and reverse-phase protein array, RPPA assays). Pharmacokinetic and pharmacodynamic (PK/PD) studies were performed in non-tumor bearing mice to assess BBB permeability and antitumor effects of MPT0B640. RESULTS: MPT0B640 inhibited proliferation of both adherent (LN229, A172, U251-HF) and patient-derived GSCs (GSC262, GSC811, GSC11, GSC23, GSC20 and GSC272) in a dose- and time-dependent fashion with an IC50 range of 50-1000 nM. MPT0B640-treated cells underwent apoptosis and/or cell cycle arrest with downregulation of pro‐survival signal kinases, phospho‐Akt, p-ERK1/2 and p-S6. PK/PD studies showed increased HSP70 expression (a marker of Hsp90 inhibition) and detectable levels of drug in brain specimens from non-tumor bearing mice after a single dose of MPT0B640, indicating BBB permeability and target inhibition of the agent. Results of ongoing animal studies assessing drug toxicity and animal survival with MPT0B640 will be presented. CONCLUSIONS: MPT0B640 is a potent HSP90 inhibitor that has potent antitumor activity against genetically heterogeneous gliomas in vitro, effectively crosses the intact BBB and demonstrates target inhibition warranting further investigation for treatment of gliomas.